2020
DOI: 10.1371/journal.ppat.1008593
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus Core protein nuclear interactome identifies SRSF10 as a host RNA-binding protein restricting HBV RNA production

Abstract: Despite the existence of a preventive vaccine, chronic infection with Hepatitis B virus (HBV) affects more than 250 million people and represents a major global cause of hepatocellular carcinoma (HCC) worldwide. Current clinical treatments, in most of cases, do not eliminate viral genome that persists as a DNA episome in the nucleus of hepatocytes and constitutes a stable template for the continuous expression of viral genes. Several studies suggest that, among viral factors, the HBV core protein (HBc), well-k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 104 publications
3
34
0
Order By: Relevance
“…Cp has notably strong interaction with SR protein kinases (which have nuclear and cytoplasmic localization) ( 52 54 ). A recent examination of the nuclear RNA-dependent interactome of HBV Cp found a statistically significant number of interactions with ribosomal proteins (enriched in the nucleolus) and spliceosomal proteins (enriched in nuclear speckles) ( 55 ). The biological relevance of Cp nucleolar localization and interactions with resident proteins needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Cp has notably strong interaction with SR protein kinases (which have nuclear and cytoplasmic localization) ( 52 54 ). A recent examination of the nuclear RNA-dependent interactome of HBV Cp found a statistically significant number of interactions with ribosomal proteins (enriched in the nucleolus) and spliceosomal proteins (enriched in nuclear speckles) ( 55 ). The biological relevance of Cp nucleolar localization and interactions with resident proteins needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high risk of recurrence and metastasis, the 5-year survival probabilities of advanced HCC are still undesirable. The epidemiology of HCC is affected by underlying liver diseases especially hepatitis B virus (HBV) ( Chabrolles et al, 2020 ). It has been estimated that HBV infection is responsible for 50% of HCC worldwide ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 1,500 human RBPs have been discovered, which possess 600 structure-specific RNA-binding domains ( Schneider et al, 2019 ). Most of them are characterized by evolutionary conservatism and ubiquitous expression to maintain cellular homeostasis ( Chabrolles et al, 2020 ). Genetic and proteomic data highlight that alterations in RBP expression display profound implications on HCC ( Lin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being involved in nucleocapsid formation in the cytoplasm, the HBV Core protein is also abundantly present in the nucleus of infected hepatocytes where it may regulate viral gene expression ( Akiba et al, 1987 ; Zhang et al, 2016 ). A recent proteomic analysis indicated that the nuclear interactome of Core was mainly composed by cellular RBPs and in particular by SR proteins, one of which, SRSF10 displays an antiviral activity ( Chabrolles et al, 2020 ). Unexpectedly, however, depleting SRSF10 or provoking its dephosphorylation does not affect HBV RNA splicing but rather modulates the level of nascent HBV RNA.…”
Section: Interplay With Viral Replicationmentioning
confidence: 99%